The Drawbacks of Prophecy in Guiding Mankind, A Critique of Islamic Doctrine of Prophethood - Hossein Atrak (Jurnal Theologia, 2022)
The belief in the prophethood and sending prophets by God to guide mankind is one of the common beliefs of divine religions. According to Islamic theologians, divine knowledge and wisdom necessitate the sending of prophets to guide mankind. This study aims to determine the logical challenges associated with this idea, and whether such a thing is expected from God taking into account His attributes. The drawbacks and challenges of prophecy in the guidance of mankind include the logical problem of miracles' indication of prophecy, the inconsistency of miracles with the claims of prophecy, the temporal and linguistic mismatch between prophets and humans, human fallibility, the prophet's interregnum in the world, the problem of exegesis of the scriptures, and the problem of multiplicity of religions and sects. On the contrary, it appears that All-wise God could have used better, simpler, and more effective ways to guide mankind, such as spiritual and instinctive guidance, direct guidance, the sending of a single eternal prophet, and angelic guidance. As a result of the numerous logical and practical flaws in the use of prophecy to guide mankind, the author believes that it seems unlikely and unacceptable that All-wise and All-knowing God has sent prophets for human guidance, and that another justification must be sought for prophecy.